Patogenicidad del hongo metarrhizium anisopliae sobre bemisia spp. - Guerrero Guerra, C.=700 1 Fonseca Flores, M.; Castella Meriño, M.I.; Suarez Soto, E.
(Es, En)
Ilus., 5 ref.
Keywords: METARRHIZIUM ANISOPLIAE; PATOGENICIDAD; BEMISIA; CUBA